Coupling of unstructured TLM and BEM for accurate 2D electromagnetic simulation - Simmons, Daniel; Cools, Kristof; Sewell, Phillip (2015)
In this paper the hybridisation of the 2D time-domain boundary element method (BEM) with the unstructured transmission line method (UTLM) will be introduced, which enables accurate modeling of radiating boundary conditions and plane wave excitations of uniform and non-uniform targets modelled by geometrically accurate unstructured meshes. The method is demonstrated by comparing numerical results against analytical results.